Long‐Lived Efficient Inverted Organic Light‐Emitting Diodes Developed by Controlling Carrier Injection Barrier into Emitting Layer. Issue 13 (4th May 2020) - Fukagawa, Hirohiko; Ito, Hirokazu; Kawamura, Shizuka; Iwasaki, Yukiko; Inagaki, Kaito; Oono, Taku; Sasaki, Tsubasa; Shimizu, Takahisa
Abstract: Inverted organic light‐emitting diodes (iOLEDs), where electrons are injected without the use of reactive metals such as alkali metals, have attracted extensive attention owing to their higher air stability than conventional OLEDs (cOLEDs). Although iOLEDs are promising for use in applications such as flexible displays, little is known about the emitting layer most suitable for improving their operational lifetime, which is one of the most important parameters for practical applications. Here, it is shown that the operational lifetimes of both iOLEDs and cOLEDs strongly depend on the hole and electron injection barriers of the emitting layer, which is clarified by synthesizing novel emitting hosts having similar molecular structures but different energy levels. The cOLED employing the novel emitting host with the largest hole injection barrier exhibits the shortest operational lifetime, whereas the iOLED employing the same emitting host exhibits the longest operational lifetime owing to the smallest electron injection barrier. The appropriate energy levels of the emitting layer can differ between iOLEDs and cOLEDs since the management conditions of the carriers, excitons, and polarons in iOLEDs are different from those in cOLEDs. A green iOLED with performance equivalent to that of state‐of‐the‐art green cOLEDs reported in the literature is first realized. Abstract : Emitting layers suitable for long‐lived inverted organic light‐emitting diodes (iOLEDs) are found to be different from those suitable for long‐lived conventional OLEDs (cOLEDs) by investigating the correlation between carrier injection barriers and characteristics of iOLEDs and cOLEDs. An efficient and long‐lived green iOLED with performance equivalent to that of state‐of‐the‐art green cOLEDs reported in the literature is first realized.